Radioactive Cs in the Severely Contaminated Soils Near the Fukushima Daiichi Nuclear Power Plant - Kaneko, Makoto; Iwata, Hajime; Shiotsu, Hiroyuki; Masaki, Shota; Kawamoto, Yuji; Yamasaki, Shinya; Nakamatsu, Yuki; Imoto, Junpei; Furuki, Genki; Ochiai, Asumi; Nanba, Kenji; Ohnuki, Toshihiko; et al. (Frontiers in Energy Research, 2015)
Radioactive Cs isotopes (137Cs, t1/2 = 30.07 years and 134Cs, t1/2 = 2.062 years) occur in severely contaminated soils within a few kilometer of the Fukushima Daiichi nuclear power plant at concentrations that range from 4 × 105 to 5 × 107 Bq/kg. In order to understand the mobility of Cs in these soils, both bulk and submicron-sized particles elutriated from four surface soils have been investigated using a variety of analytical techniques, including powder X-ray diffraction analysis, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and analysis of the amount of radioactivity in sequential chemical extractions. Major minerals in bulk soil samples were quartz, feldspar, and minor clays. The submicron-sized particles elutriated from the same soil consist mainly of mica, vermiculite, and smectite and occasional gibbsite. Autoradiography in conjunction with SEM analysis confirmed the association of radioactive Cs mainly with the submicron-sized particles. Up to ~3 MBq/kg of 137Cs are associated with the colloidal size fraction (<1 μm), which accounts for ~78% of the total radioactivity. Sequential extraction of the bulk sample revealed that most Cs was retained in the residual fraction, confirming the high binding affinity of Cs to clays, aluminosilicate sheet structures. The chemistry of the fraction containing submicron-sized particles from the same bulk sample showed a similar distribution to that of the bulk sample, again confirming that the Cs is predominantly adsorbed onto submicron-sized sheet aluminosilicates, even in the bulk soil samples. Despite the very small particle size, aggregation of the particles prevents migration in the vertical direction, resulting in the retention of >98% of Cs within top ~5 cm of the soil. These results suggest that the mobility of the aggregates of submicron-sized sheet aluminosilicate in the surface environment is a key factor controlling the current Cs migration in Fukushima.